Penegakan Hukum oleh Kepolisian Resor Langkat terhadap Pembalakan Liar (Illegal Logging) di Wilayah Hukum Polres Langkat - Herman Frenky Sinaga; Ediwarman Ediwarman; M Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Human activities that cause environmental damage, one of which is illegal logging or illegal logging, which is an act of exploitation by humans on forests, causing damage to forest ecosystems. This study aims to determine the factors that cause illegal logging in the Langkat Police jurisdiction and the policies carried out by the Police in law enforcement against illegal logging in the Langkat Police jurisdiction. The research method used is descriptive method, using qualitative descriptive data analysis techniques. The results showed that the factors that caused illegal logging in Langkat Regency were internal factors, consisting of economic factors and the lack of public awareness of the environment, and external factors, consisting of high wood prices, high wood demand, weak supervision, law enforcement is not strict. The policies carried out by the Langkat Police in law enforcement against the crime of illegal logging consist of penal policies, namely reporting illegal logging, following up on illegal logging, going to illegal logging locations, securing evidence, catching illegal timber trucks. Non-penal policies include socializing the prohibition of illegal logging, increasing community participation, supervising timber trucks, examining suspects, developing cases, and transferring files.